Numerical Simulation of Hemodynamics in Two Models for Total Anomalous Pulmonary Venous Connection Surgery - Cheng, Yeyang; Qiao, Aike; Yang, Yao; Fan, Xiangming (Frontiers in Physiology, 2020)
Objective: To numerically compare the prospective hemodynamic outcomes between a new window surgery and a traditional surgery in the treatment of supracardiac total anomalous pulmonary venous connection (S-TAPVC). Methods: A 3D geometry model, composed of pulmonary vein (PV) and left atrium (LA), was reconstructed from medical images of a patient with S-TAPVC. Two surgery models were established based on this model. One is the traditional surgery model, where an elliptical anastomosis was created by incising and stitching the LA and the common vein along the axis of the common vein. The other is the new window surgery model, where the common vein was incised with an H-shaped orifice, and LA was incised with a transposed H-shaped orifice, and then the orifice edges were stitched like a window. Two models with a relative cross sectional area (RCSA) of 300 mm2/m2 and 500 mm2/m2 were established, which correspond to traditional surgery and window surgery. Numerical simulation of hemodynamics was carried out. The velocity, left atrium and pulmonary vein pressure, the pressure difference of anastomosis and the energy conversion efficiency were analyzed to evaluate the prospective hemodynamic outcomes of these two operations. Results: Window surgery presented a lower blood flow velocity, pressure difference, and the WSS at the anastomosis, compared to traditional surgery. In terms of energy loss, the power conversion efficiency of window surgery was significantly higher than that of traditional surgery, with 66.8% and 53.5% respectively. Conclusions: The new window surgery demonstrates a lower pressure difference of anastomosis and higher energy conversion efficiency, which may be a better choice compared with the traditional surgery for S-TAPVC patient.